BESTUURS PLAN DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA PEKANBARU DALAM PERLINDUNGAN ANAK TAHUN 2018 - Pratama, Fikri Adytia; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Cases of violence against children that occur indicate the need for comprehensive treatment. Comprehensive handling will then be arranged by the authorized government. The purpose of this study is to see the Bestuurs Plan for the Office of Women's Empowerment and Child Protection in the city of Pekanbaru in the protection of children in 2018. And to find out what are the obstacles of the Office of Women's Empowerment and Child Protection in preparing plans that have been designed in 2018. This study uses qualitative methods with descriptive analysis case study. Data collection techniques uses interviews as primary data and literature study as secondary data.The theoretical concept used by researchers is the Bestuurs Plan which has indicators in the four basic stages of planning, namely, setting goals or a series of objectives, formulating the current situation, identifying all facilities and obstacles, compiling steps to achieve goals. This research uses qualitative research methods, with descriptive data review. In collecting data, researchers used interview techniques, and documentation.The results of this study indicate that, planning for the Office of Women's Empowerment and Child Protection of Pekanbaru City in child protection in 2018 had not been optimal. This can be seen from the realization of the budget for conducting programs to protect children that are still lacking from the established budget plan. In addition, regulatory and institutional barriers to child protection become an obstacle for the preparation of planning for child protection for the Pekanbaru City Women's Empowerment and Child Protection Agency. This is caused by factors such as lack of human resources in the service unit. Keywords : Bestuurs Plan, Stages of Planning, Child Protection.